Hodulík, Jakub: Ústavní zákaz cenzury v teorii a praxi [Constitutional Prohibition of Censorship in Theory and Practice] - Petr Gangur (Bratislava Law Review)
The concept of censorship is clearly used widely and frequently by politicians, but it is also at the heart of modern legal debates relating to the freedom of expression of individuals on social media. But what is censorship? Do legal scholars and politicians use the term correctly or are there instances when the term censorship is used too broadly and without a relevant legal basis?